Use of Flexible Bronchoscopy in Foreign Body Aspiration - Gökçen Ünal; Aslı İmran Yılmaz; Tahir Tok; Sevgi Pekcan (Turkish Archives of Otorhinolaryngology, 2022)

(untitled)
Objective:Foreign body aspiration remains a serious health problem with a potential for severe consequences, and acute and chronic problems in children. It therefore demands immediate intervention. Rigid bronchoscopy has long been the method of choice for foreign body removal but is now being replaced by flexible bronchoscopy which offers reduced trauma and the ability to access distal bronchial regions. In the presented study we assessed the patients who underwent flexible bronchoscopy for foreign body removal in our clinic.Methods:We reviewed the records of 20 patients who underwent flexible bronchoscopy due to suspected foreign body aspiration and had a foreign body removed in our clinic. Patients were analyzed in terms of sociodemographic data, foreign bodies removed, method of foreign body removal, foreign body location and time to diagnosis.Results:Our study group included nine females and 11 males. The removed foreign body was organic in 19 of the 20 patients and inorganic in one patient. Hard organic food, such as hazelnuts, peanuts, seeds, almonds, and raw corn kernel were identified in 12 patients, a piece of fishbone in one patient and a piece of gelatin in another. The pieces of soft organic food identified were apple in one patient, egg in one patient, and boiled corn kernel in one patient and removed by suction. The foreign body was removed using forceps in nine patients, and a basket was used successfully in seven patients.Conclusion:Foreign bodies can be removed with minimal complication using flexible bronchoscopy, basket, and forceps in children.